Efektivitas penerapan model PBL berbasis wordwall - Mufadhilah, Badiatul; Sutriyani, Wulan (Jurnal Gentala Pendidikan Dasar, 2025)
The purpose of this study was to determine the effectiveness of the use of the Wordwall-based PBL model on the learning outcomes of mathematics in multiplication material for grade 3 students of SD Negeri 9 Jambu, Mlonggo. This study used a quantitative method and a one-group pretest and posttest design. By comparing the implementation before and after the application of the Wordwall-based Problem Based Learning (PBL) model. All grade 3 students became research subjects through saturated sample techniques. Collecting data through pretest, posttest. The results showed that before the application of Wordwall-based PBL was 67.34, while after the application it increased significantly to 89.06. This increase was strengthened by the results of the hypothesis with a significant value <0.001, which means less than 0.05. The conclusion is that there was a significant increase in understanding after the treatment of the Wordwall-based Problem Based Learning model was applied to mathematics learning on the multiplication material of whole numbers in grade 3 of SD Negeri 9 Jambu, Mlonggo.